Ig-Like Transcript 2 (ILT2) Blockade and Lenalidomide Restore NK Cell Function in Chronic Lymphocytic Leukemia - Villa-Álvarez, Mónica; Sordo-Bahamonde, Christian; Lorenzo-Herrero, Seila; Gonzalez-Rodriguez, Ana P.; Payer, Angel R.; Gonzalez-Garcia, Esther; Villa-Álvarez, María C.; López-Soto, Alejandro; Gonzalez, Segundo (Frontiers in Immunology, 2018)
One of the cardinal features of chronic lymphocytic leukemia (CLL) is its association with a profound immunosuppression. NK cell function is markedly impaired in CLL patients, who show a significant dysregulation of the expression of activating and inhibitory receptors. Here, we analyzed the role of the novel inhibitory receptor Ig-like transcript 2 (ILT2, also termed LIR-1, LILRB1) in the regulation of NK cells in CLL. Our results show that ILT2 expression was significantly decreased on leukemic cells and increased on NK cells of CLL patients, particularly in those with advanced disease and with bad prognostic features, such as those carrying chromosome del(11q). The immunomodulatory drug lenalidomide may regulate the expression of ILT2 and its ligands in CLL since it significantly increased the expression of ILT2 and partially reestablished the expression of its ligands on leukemic cells. Furthermore, lenalidomide did not alter the expression of ILT2 on NK cells, but it significantly increased their activation and proliferation, which was strongly enhanced by ILT2 blockade. Combining ILT2 blockade and lenalidomide activated NK cell cytotoxicity resulting in increased elimination of leukemic cells from CLL patients. Overall, we describe herein the role of an inhibitory receptor involved in the suppression of NK cell activity in CLL, which is restored by ILT2 blockade in combination with lenalidomide, suggesting that it may be an interesting therapeutic strategy to be explored in this disease.